LEGAL PROTECTION FOR GRANT RECIPIENTS FOR DELAY IN REGISTRATION OF PPAT DEEDS IN TRANSFER OF LAND RIGHTS - Anastasia Risca Kusumawardani; Jamal Wiwoho; Waluyo (Journal of International Islamic Law, Human Right and Public Policy, 2026)
A grant is a free gift from the grantor to the grantee made while both parties are still alive. The grant agreement is the authority of the Land Deed Making Officer (PPAT) which is also stated in Article 40 of Government Regulation Number 24 of 1997 concerning Land Registration that the PPAT has an obligation to register the deed of grant he made and submit the deed along with the relevant documents to the Land Office no later than 7 (seven) working days from the date of signing the deed in question. However, there are still PPATs who are negligent in complying with these regulations, resulting in delays in registering the deed of grant to the Land Office, of course, this negligence causes losses for the grantee. This study aims to analyze the legal consequences of the delay in registering the deed of grant by the Land Deed Making Officer (PPAT) on the status of transfer of land rights and to examine the form of legal protection for the grantee regarding the delay in registering the deed of grant. The research method used is normative juridical legal research with a statutory approach and a case approach with this research being prescriptive. The results of the study indicate that the delay in registering the deed of gift results in the inability to transfer land rights, so that the transfer of rights is not recorded administratively with the land rights still registered in the name of the grantor. This also has an impact on the weak legal position of the grantee and has the potential to cause disputes such as blocking the grant object by the grantor, in this case the grantee does not get legal certainty because the transfer of rights cannot be continued. Although the deed of gift has been signed, it remains valid despite the delay in registration, but the deed has not yet transferred rights, therefore the grantee does not have legal force over the grant object. Furthermore, this negligence can result in the opportunity for disputes because the grantee has not been legally registered as the owner of the rights to the grant object legally. Legal protection for grantees consists of preventive and repressive protection. Preventive protection is obtained through the existence of regulations regarding registration obligations by PPAT within a predetermined time period, while repressive protection is provided by filing a lawsuit with the court and demanding compensation against the PPAT for his negligence. Thus, it is necessary to increase awareness of compliance by PPAT in carrying out his duties and authorities, including his obligations, as well as legal protection for grantees.